Institutions: Evolution, Path Dependency, Anachronisms and Impact. Issue 2 (1st February 2016) - Dimova, Ralitza; Savoia, Antonio
Abstract: This Special Section builds on cutting edge developments in the literature on institutional change and its link to economic development. It throws fresh light on this link from both a microeconomic (firm and household level) and a macroeconomic (country and cross country level) perspective. The main message is that understanding the dynamics of institutional change is key to understanding the process of economic development, while understanding evolving institutions and their links to economic development requires an understanding of the state of flux and the heterogeneous characteristics of individual settings.